Accountability Denied: Bangladesh’s Engagement with International Human Rights Bodies on Enforced Disappearances - Rezwan Khair Fahim (Law and Society Students' Journal)
This article examines Bangladesh’s interaction with international human rights mechanisms, especially the ICCPR, CAT, UPR, and WGEID, highlighting the issue of enforced disappearances. The analysis applying Creamer and Simmons’ framework of elite socialization, learning and capacity building, domestic mobilization, and law development reveals persistent state denial, mislabeling of crimes, and rejection of recommendations. Despite treaty obligations, Bangladesh’s government dismissed allegations as politically motivated, refused to criminalize enforced disappearance and evaded scrutiny. While civil society efforts and international pressure increased visibility, systemic repression, and judicial inaction stifled accountability. The study underscores the limitations of non-binding mechanisms in authoritarian contexts, where political will determines compliance. The 2024 interim government’s ratification of ICPPED signals potential reform, yet meaningful progress hinges on domestic legal reforms and dismantling institutionalized impunity.